Re-cosmetic: a mobile system for cosmetic consumers - Nor Aliah, Noor Azman; Nur Sabrina Fasha, Zaidi Sham; Abd Rahim, Noor Hayani (Universiti Kuala Lumpur Publishing, 2023)
In this day and age, the demand for cosmetics has escalated which means a lot of cosmetics containers have been produced. In conjunction with this, inappropriate cosmetic waste disposal has contributed to more plastic waste which takes many years to decompose. Hence, this project which includes the development of a mobile application system namely ‘Re-cosmetic’ is dedicated to responding to the Sustainable Development Goal 12 mission statement which is to ensure sustainable consumption and production patterns. This project involves literature review based on the existing systems, the analysis and design of the pre-production of system development, documentation on User Acceptance Test as well as overall conclusion from this project. The main features of this system include the recycle processor, newsfeed, point transfer and rewarding,cashback system as well as reminder. This system is developed using React Native, Visual Studio Code and Firebase.